1977
DOI: 10.1111/j.1476-5381.1977.tb06989.x
|View full text |Cite
|
Sign up to set email alerts
|

The Effects of Glucagon, Secretin, Pancreozymin and Pentagastrin on the Hepatic Arterial Vascular Bed of the Dog

Abstract: 1The sympathetically-innervated arterial vascular bed of the dog's liver was perfused from a femoral artery. Arterial blood flow and perfusion pressure were monitored continuously and the hepatic arterial vascular resistance (HAVR) calculated from these measurements. 2 Commercial preparations of secretin, pancreozymin, glucagon and pentagastrin were administered by intra-arterial (i.a.) injection and infusion. 3 Secretin and pancreozymin by injection caused dose-dependent hepatic arterial vasodilatation, and o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

1977
1977
2007
2007

Publication Types

Select...
3
2
1

Relationship

1
5

Authors

Journals

citations
Cited by 27 publications
(11 citation statements)
references
References 22 publications
0
11
0
Order By: Relevance
“…The use of the sympathetically-innervated arterial vascular bed of the dog's liver for the quantitative study of the effects of vasodilator hormones has previously been reported from this laboratory, and the relative molar potencies of a range of naturallyoccurring and synthetic vasodilator agents established (Richardson & Withrington, 1976c, d;1977a). In the present experiments, this preparation has been used to study the vascular effects of noradrenaline and adrenaline, injected intra-arterially, comparing these with the synthetic a-and P-adrenoceptor agonists, phenylephrine and isoprenaline respectively.…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…The use of the sympathetically-innervated arterial vascular bed of the dog's liver for the quantitative study of the effects of vasodilator hormones has previously been reported from this laboratory, and the relative molar potencies of a range of naturallyoccurring and synthetic vasodilator agents established (Richardson & Withrington, 1976c, d;1977a). In the present experiments, this preparation has been used to study the vascular effects of noradrenaline and adrenaline, injected intra-arterially, comparing these with the synthetic a-and P-adrenoceptor agonists, phenylephrine and isoprenaline respectively.…”
Section: Discussionmentioning
confidence: 99%
“…Whilst it may be that the hepatic arterial vasodilatation is a secondary effect of /3-adrenoceptor-mediated stimulation of liver metabolism, the two effects, both mediated by /3-adrenoceptors may well have distinct receptor sites. It seems probable that the vasodilator action of adrenaline is of physiological importance in ensuring an adequate blood flow to the hepatic parenchyma in states of stimulated liver metabolism; in this context, the study of the effects of intra-arterial infusions of catecholamines which may more closely mimic the physiological release of suprarenal medullary catecholamines than acute injections, may be of importance, as may the possible interactions between adrenaline and other hormones such as glucagon (Richardson & Withrington, 1976a, c;1977a).…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations